Potentially Beneficial Effect of Hydroxychloroquine in a Patient with a Novel Mutation in Protein Kinase C delta Deficiency - ÖZEN, AHMET OĞUZHAN; YÜCELTEN, AYŞE DENİZ; AYDINER, ELİF; ÖĞÜLÜR, İSMAİL; BARIŞ, SAFA (SPRINGER/PLENUM PUBLISHERS, 2015)
Protein kinase C delta (PRKCD) has essential functions in controlling B-cell proliferation and apoptosis, development of B-cell tolerance and NK-cell cytolitic activity. Human PRKCD deficiency was recently identified to be causative for an autoimmune lymphoproliferative syndrome like disorder with significant B-cell proliferation particularly of immature B cells. Here we report a child with a novel mutation in PRKCD gene who presented with CMV infection and an early onset SLE-like disorder which was successfully treated with hydroxychloroquine.
Keywords: Protein kinase delta c; lupus-like disorders; autoimmunity; T-CELLS; INDUCED APOPTOSIS; PKC-DELTA; AUTOIMMUNITY; INVOLVEMENT; MECHANISM